Osteogenic Differentiation of hDPSCs on Biogenic Bone Apatite Thin Films. (22nd October 2017) - Bianchi, Michele; Pisciotta, Alessandra; Bertoni, Laura; Berni, Matteo; Gambardella, Alessandro; Visani, Andrea; Russo, Alessandro; de Pol, Anto; Carnevale, Gianluca
Abstract : A previous study reported the structural characterization of biogenic apatite (BAp) thin films realized by a pulsed electron deposition system by ablation of deproteinized bovine bone. Thin films annealed at 400°C exhibited composition and crystallinity degree very close to those of biogenic apatite; this affinity is crucial for obtaining faster osseointegration compared to conventional, thick hydroxyapatite (HA) coatings, for both orthopedics and dentistry. Here, we investigated the adhesion, proliferation, and osteogenic differentiation of human dental pulp stem cells (hDPCS) on as-deposited and heat-treated BAp and stoichiometric HA. First, we showed that heat-treated BAp films can significantly promote hDPSC adhesion and proliferation. Moreover, hDPSCs, while initially maintaining the typical fibroblast-like morphology and stemness surface markers, later started expressing osteogenic markers such as Runx-2 and OSX. Noteworthy, when cultured in an osteogenic medium on annealed BAp films, hDPSCs were also able to reach a more mature and terminal commitment, with respect to HA and as-deposited films. Our findings suggest that annealed BAp films not only preserve the typical biological properties of stemness of, hDPSCs but also improve their ability of osteogenic commitment.